Sleuth : Obey The Rules - Caine, Michael; Law, Jude, 1972-; Pinter, Harold, 1930-2008 ([Place of publication not identified] : Sony Pictures Home Entertainment, 2008)
Directed by critically-acclaimed director Kenneth Branagh, Jude Law and two-time Oscar-winner Michael Caine (1987, Best Supporting Actor, Hannah and Her Sisters; 2000, Best Supporting Actor, Cider House Rules) join forces in this sharp-witted, modern adaptation of the 1972 classic, Sleuth. Locked in a high-tech English manor, bound in a deadly duel of wits, Andrew Wyke (Caine) and Milo Tindle (Law) come together as English gentlemen to discuss the matter of Wyke's wife: the woman both are sleeping with. But as wit becomes wicked and clever becomes cutthroat, Wyke and Tindle's game of one-upmanship spirals out of control, in an escalating chess match that can have only one outcome: murder.